Rancang Bangun Aplikasi Penjualan Gorden Berbasis Web Menggunakan Metode Rational Unified Process - Septiana, Yosep; Yusuf, David (Jurnal Algoritma, 2025)
Rapid technological advances in the millennial era have a significant impact on business, including curtain sales. KUD Kadungora Curtains shop still relies on cellphones to manage the business, which is less than optimal. Manual recording of transactions causes the risk of loss or damage to data, making it difficult to compile accurate sales reports. This study aims to design a web-based curtain sales application using the Rational Unified Process (RUP) method to improve the efficiency and transparency of reporting for the KUD treasurer and sales management. This application is designed to be mobile-friendly to make it easier for shop owners to manage sales, stock items, curtain orders, and reporting. The results of testing with Blackbox testing at the alpha stage showed valid status, while the beta testing stage by two respondents showed user satisfaction by calculating the SUS (System Usability Scale) value of 90, indicating that this application is very good and according to user needs.